Natural weathering of hemp fibers reinforced polypropylene biocomposites: Relationships between visual and surface aspects, mechanical properties and microstructure based on statistical approach. (20th October 2018) - Badji, Célia; Beigbeder, Joana; Garay, Hélène; Bergeret, Anne; Bénézet, Jean-Charles; Desauziers, Valérie
Abstract: Two natural weathering of neat polypropylene (PP) and hemp fibers reinforced PP biocomposites were investigated. The objective was to emphasize the relationships between the properties of materials according to the fiber loading and the weathering time in order to bring new insights of degradation mechanisms understanding. For this purpose, a Principal Component Analysis (PCA) method was applied to the dataset. The treatment carried out by isolating materials loaded by the three different hemp fiber rates particularly outstand the link between mechanical properties and products issued from oxidation. The close correlation between whitening parameter and CC bond level also confirmed the lignin degradation way. Finally, depending on the weathering duration, the properties characterized either fiber loading or weathering state (unweathered or weathered) whereas mechanical performance differentiated the three different non-weathered samples whatever the exposure time.